2017
DOI: 10.1186/s41936-017-0005-3
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-aminobutyric acid ameliorates gamma rays-induced oxidative stress in the small intestine of rats

Abstract: Background: The current study aimed to evaluate the role of gamma-amino butyric acid (GABA) in modulating histopathological and biochemical disturbances in the rat's small intestine following gamma radiation exposure. Results:The results showed that whole body gamma irradiation (6 Gy) of rats induced mucosal damage, hemorrhage, increased cellularity of the lamina propria layer with areas of complete ulcerations. Histopathological changes were associated with a significant increase in malondialdehyde (MDA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
(39 reference statements)
1
8
0
Order By: Relevance
“…Such pronounced potential of the supernatant to protect tight junction proteins from deleterious effect of inflammation is in accordance with the recent results related to GABA potential to improve the gut barrier function, acting through selective up-regulation of Mucin-1 protein in isolated pig jejunum ( Braun et al, 2015 ). Additionally, El-Hady et al (2017) demonstrated that GABA administration reduced the degenerative changes in the jejunal epithelial cells and significantly improved the survival of villi and crypts in gamma-irradiated rats. Considering this we further investigated whether BGZLS10-17 supernatant with highest GABA concentration (4 mM), supernatant with addition of 4mM artificial GABA, and supernatant without GABA, may have affect on IL-1β induced IL-8 production by differentiated Caco-2 cells monolayer.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Such pronounced potential of the supernatant to protect tight junction proteins from deleterious effect of inflammation is in accordance with the recent results related to GABA potential to improve the gut barrier function, acting through selective up-regulation of Mucin-1 protein in isolated pig jejunum ( Braun et al, 2015 ). Additionally, El-Hady et al (2017) demonstrated that GABA administration reduced the degenerative changes in the jejunal epithelial cells and significantly improved the survival of villi and crypts in gamma-irradiated rats. Considering this we further investigated whether BGZLS10-17 supernatant with highest GABA concentration (4 mM), supernatant with addition of 4mM artificial GABA, and supernatant without GABA, may have affect on IL-1β induced IL-8 production by differentiated Caco-2 cells monolayer.…”
Section: Resultsmentioning
confidence: 95%
“… Braun et al (2015) proposed that the positive effects of glutamine on intestinal integrity are partly attributable to the promoting effects of its metabolite GABA on the expression of protective mucin in enterocytes. El-Hady et al (2017) showed that administrated GABA have a role in improving histopathological and biochemical disturbances in the rat’s small intestine following gamma radiation. Considering protective effects of GABA on stressed enterocytes showed in these studies as well as repeatedly proven positive effect of different Lactobacillus strains, we aimed to investigate the effects of GABA-producing Lactobacillus strain on enterocytes exposed to inflammatory condition in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, the protective effect of Gaba against H 2 O 2 -induced oxidative stress in pancreatic cells [89] and human umbilical vein endothelial cells [90] was observed via reducing cell death, inhibiting reactive oxygen species (ROS) production, and enhancing antioxidant defense systems. Similarly, gamma rays-induced oxidative stress in the small intestine of rats was significantly ameliorated via decreasing malondialdehyde and advanced oxidation protein productions, increasing catalase and glutathione peroxidase activities, preventing mucosal damage and hemorrhage, and inducing the regeneration of the small intestinal cells [91]. Gaba also attenuated brain oxidative damage associated with insulin alteration in streptozotocin-treated rats [92].…”
Section: Pharmaceutical Properties Of Gabamentioning
confidence: 99%
“…Several preventive trials were established trying to decrease the chance of GIT mucosa ulcerations or to enhance re-epithelialization of the lesions to facilitate their recovery. [ 20 ] In the present research, we administered ZO in accompany with alcohol intake to investigate its preventive effect on the mucosa of rat jejunum. The results were promising, where nearly normal jejunal architecture were detected in ZO alcohol group with slight affection of the jejunal mucosa in the form of few areas of ulceration of the top of some villi and few enterocytes showed loss of their covering brush microvillous border.…”
Section: Discussionmentioning
confidence: 99%